2021
DOI: 10.3389/fsurg.2021.704902
|View full text |Cite
|
Sign up to set email alerts
|

T1 Bladder Cancer: Comparison of the Prognostic Impact of Two Substaging Systems on Disease Recurrence and Progression and Suggestion of a Novel Nomogram

Abstract: Background: The T1 substaging of bladder cancer (BCa) potentially impacts disease progression. The objective of the study was to compare the prognostic accuracy of two substaging systems on the recurrence and progression of primary pathologic T1 (pT1) BCa and to test a nomogram based on pT1 substaging for predicting recurrence-free survival (RFS) and progression-free survival (PFS).Methods: The medical records of 204 patients affected by pT1 BCa were retrospectively reviewed. Substaging was defined according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In contrast, our study used CSS as the outcome and only included DMUBC, which may be the main reason for the different results. Asimakopoulos et al performed a retrospective study and developed a prognostic nomogram that confirmed T1 substaging, tumor size and tumor location as independent prognosticators of five-years disease-free survival in T1 bladder cancer patients[ 20 ]. Additionally, Tian et al included TCBC patients from SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study used CSS as the outcome and only included DMUBC, which may be the main reason for the different results. Asimakopoulos et al performed a retrospective study and developed a prognostic nomogram that confirmed T1 substaging, tumor size and tumor location as independent prognosticators of five-years disease-free survival in T1 bladder cancer patients[ 20 ]. Additionally, Tian et al included TCBC patients from SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…The demographics of each included study are shown in Table 1 and Table S2. Of the 72 included studies, five included only Ta NMIBC patients [12–16], and 26 studies included only T1 NMIBC patients [17–42]. The other 41 studies included both Ta and T1 patients [43–83].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on semiquantitative methods included in our comprehensive literature review summarizing over 3700 patients showed an association with progressionfree survival or cancer-specific survival. 12,18,32,[44][45][46][47][48]51,52 Only 7% of studies on T1 subcategorization failed to show such an association, 13,14,20,26,36,39,44 most of which applied histoanatomic methods. Studies, comparing head-to-head histoanatomic and semiquantitative methodology also revealed a better performance in terms of prognostic impact for the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data support T1 subcategorization as a predictor of oncological outcome 2–54 . Several studies have been conducted to identify the prognostic role of lamina propria invasion and to determine the best method to assess T1 subcategorization 9–54 . The 2 main approaches applied for bladder T1 subcategorization are histoanatomic methods using the presence of muscularis mucosae (MM) as a landmark, and (semi)quantitative methods using ocular micrometer or high-power fields–based assessment of extent of invasion 9–54 .…”
mentioning
confidence: 99%